“Green and Clean” di Ekowisata Subak Uma Lambing Desa Sibang Kaja, Kecamatan Abiansemal, Kabupaten Badung - Risadi, Md. Yudyantara; Nuriawan, I Nengah Alit; Ariputra, I Putu Suyasa; Widana, I Ketut Arta; Darma, I Gusti Ketut Indra Pranata; Sudarningsih, Ni Komang (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This community service activity examined the role of the green and clean movement within the context of ecotourism development in Subak Uma Lambing, located in Abiansemal District, Badung Regency. Ecotourism has become a central focus of sustainable development efforts in the region, with Subak Uma Lambing emerging as one of its primary destinations. The objective of this study is to explore how the green and clean concept contributes to the growth and sustainability of ecotourism in this area. A mixed-methods approach was employed, combining field research with literature analysis. Primary data were collected through interviews with key stakeholders, including subak adminitrator (pekaseh), subak farmers, and environmental activists operating in the surrounding area. Secondary data were sourced from academic and policy literature related to ecotourism, environmental management, and the green and clean initiative. The findings showed that the green and clean concept plays a significant role in the development of ecotourism in Subak Uma Lambing. Initiatives such as plastic and organic waste management, nature conservation, environmental education, and community participation have been instrumental in raising awareness about the importance of environmental and cultural preservation. Moreover, the green and clean movement has contributed to the creation of new economic opportunities through the establishment of sustainable, community-based enterprises. The collaboration between the green and clean movement and ecotourism has yielded positive outcomes in preserving the environmental and cultural integrity of Subak Uma Lambing. In the long term, these sustainable efforts are expected to ensure the continued viability of ecotourism in the region, grounded in strong principles of sustainability while simultaneously delivering economic and social benefits to the local community.